(untitled) (Research Nepal Journal of Development Studies, 2023)
Madhypurthimi is one of the oldest city in the centre of Kathmandu, Kageswarimanahara, Lalitpur, Bhaktapur, Suryavinayak, Chanhgunarayan, and Mahalaxmi Municipalities of Kathmandu valley. Being such a centrally located venue with historical cultural heritage and values tourism potentiality, the tourist arrival is not satisfactory. Thus to identify the tourism potentiality of historic city Madhyapurthimi, the study has been conducted. The desk study, field survey, focus group discussion, workshop and interactions have been conducted in different occasion to find out the tourism potentials. Agriculture, Art and architecture, Cultural dances and shows, Historical heritage walks, Mask making, Open living museum, Pottery, River and Jungle in city, Riverside walk, Theme all, Tigani Baji, and Vermilion and other festivals are the major tourism products must be sold to the potential tourists inbound as well as outbound.